Asymptotic Properties of Third-Order Delay Trinomial Differential Equations - J. Džurina; R. Komariková (Abstract and Applied Analysis)
The aim of this paper is to study properties of the third-order delay trinomial differential equation ((1/r(t))y′′(t))′+p(t)y′(t)+q(t)y(σ(t))=0, by transforming this equation onto the second-/third-order binomial differential equation. Using suitable comparison theorems, we establish new results on asymptotic behavior of solutions of the studied equations. Obtained criteria improve and generalize earlier ones.